Lingual Artery Pseudoaneurysm after Total Laryngectomy: A Case Report - Gayathri Lekshmi; Santhi Thankappan Pillai; Susan James (Journal of Clinical and Diagnostic Research, 2024)
Pseudoaneurysm of the lingual artery is an extremely rare condition, and the most common causes are trauma, inflammation, neoplasm, or iatrogenic factors. An aneurysm refers to a weakening of an artery wall that creates a bulge or distention of the artery. Aneurysms of the external carotid artery and its branches are rare, comprising only 2.2% of cervical carotid aneurysms, with an even rarer occurrence of mycotic pseudoaneurysm. The superficial temporal artery and facial artery are the most commonly involved branches. Pseudoaneurysms of the lingual artery are an extremely rare entity and are often a consequence of neck surgery, trauma, inflammation, chemoradiotherapy, or odontogenic infection. They may cause life-threatening bleeding. Hereby, the authors present the case of a 47- year-old male patient with biopsy-proven Squamous Cell Carcinoma (SCC) of the hypopharynx who underwent total laryngectomy with Pectoralis Major Myocutaneous Flap (PMMC) reconstruction. The patient presented with a chief complaint of massive bleeding from the oral cavity three weeks post-procedure. The patient was immediately managed conservatively and started on inotropes. Computed Tomography (CT) angiogram of the neck showed a well-defined rounded enhancing structure in relation to the right lingual artery, with enhancement comparable to a vascular structure suggestive of a pseudoaneurysm. The patient underwent lingual artery embolisation, resulting in complete occlusion of the pseudoaneurysm. It is difficult to diagnose and manage lingual artery pseudoaneurysms, and they can cause severe distress to patients when bleeding occurs. To prevent morbidity and mortality associated with lingual artery aneurysms, they must be diagnosed and treated as early as possible.